ETOS KERJA ISLAM DAN BUDAYA ORGANISASI: PENGARUHNYA TERHADAP KINERJA KARYAWAN MULTIFINANCE SYARI’AH (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2019)
This study aims to investigate the influence of Islamic work ethics and organizational culture on employee performance at Shari’ah Multifinance Lampung. The samples were done nonprobability sampling with purposive sampling method and then analyzed using multiple regression analysis. The result show that the application of Islamic work ethics positively influenced on employee performance. its known from the t test value (2.463) more than t table (2.040). On the other hand, organizational culture negatively effected on employee performance. its known from the t test value (-2.577) less than t table (2.040). Than, simultaneously both on the variable have a positive significant effect on employee performance known from the F test value (3.686) is more than F table (2.90).